Reconciling international priorities with local needs: Denmark as a new security actor in the Gulf of Guinea - Jessica Larsen; Christine Nissen (Danish Institute for International Studies (DIIS), 2018)
In December 2018, Denmark published a new priority paper guiding its future engagement in the Gulf of Guinea to combat piracy and other types of maritime crime. Against such background, this DIIS report presents the main challenges to maritime security in the region and maps the actors and activities addressing it in order to draw out the role that Denmark should play in this context. The report shed light on the regional and international strategies and interventions that are at play at a time when Denmark is a relatively new actor in the process of defining its role in the region's maritime security infrastructure. As such, the report offers Denmark three sets of pointers for how to prioritise its activities in the Gulf of Guinea: Regionalise engagement by promoting local ownership. Focus on the "in between" by enhancing coordination and deconfliction. Look landward by strengthening legal structures.
Keywords: 300